Evaluation of Novel N-(Dibenzylcarbamothioyl) benzamide Derivatives as Antibacterial Agents by Using DFT and Drug-Likeness Assessment - Misral, H; Sapari, S; Rahman, T; Ibrahim, N; Yamin, BM; Hasbullah, SA (Hindawi Ltd, 2024)
Isomers of monothioureas, 2a-2d, derived from the reaction of disubstituted benzoyl isothiocyanate and dibenzylamine were synthesised and characterised by using elementary analysis CHNS and IR, H-1 NMR, and C-13 NMR spectroscopies. The compounds were screened for their in vitro antibacterial activity by using selected Gram-positive bacteria, and moderate inhibition activity was displayed for compound 2b with the value of inhibition zone 11 +/- 0.8 mm at a concentration of 50 mg/ml. The outcomes of Lipinski's rule of five assessment appeared to be in agreement with all compounds as they adhered to most of the rules, in which they can be preliminarily classified as active drug-like. The frontier molecular orbitals (HOMO and LUMO) for halogen-substituted 3,4-dichloro (2a) and 3,4-difluoro (2b) were also determined by applying the computational method of density functional theory (DFT) to determine their relationship as a molecular descriptor in antibacterial activities. The value of LUMO energy for compound 2b (1.8229 eV) is lower than that of compound 2a (1.8492 eV) which indicates higher antibacterial activities.